Misconception: The Experience of Pregnancy for Women with Intellectual Disabilities - Rachel Mayes; Gwynnyth Llewellyn; David McConnell (Scandinavian Journal of Disability Research, 2007)
The experience of pregnancy and motherhood, from a woman's point of view, has only been considered worthy of research in recent decades. In this time, a small number of studies have examined the experiences of mothers with intellectual disabilities. No study to date has focussed on the lived experiences of pregnancy for women with intellectual disabilities. This paper reports findings from a phenomenological study into becoming a mother for women with intellectual disabilities. We focus on the stories of three Australian women with intellectual disabilities about their experiences of being pregnant. Three key themes of the pregnancy experience for these women are illuminated. First, through experiencing their pregnant bodies the women began to understand themselves as mothers. Secondly, the women actively made decisions regarding how their baby would be cared for. Thirdly, the women involved trusted others in these important decisions. This paper gives voice to a group of marginalized women whose views about being pregnant have traditionally been silenced and/or ignored.